Effect of different harvest times and processing methods on the vitamin content of Leymus - Wang, Yifan; Chen, Xue; Zhuo, Xingliang; Wang, Lei; Jia, Tingting; Ji, Fangcai; Zhang, Hongrui; Yu, Zhu (Frontiers in Nutrition, 2024)
Objectives:The objective of this study was to investigate the effect of different harvest times and processing methods on the B vitamins and α-tocopherol contents of Leymus chinensis (Trin.). Methods: L. chinensis was harvested on 11 July (T1 group), 16 July (T2 group), 21 July (T3 group), 26 July (T4 group), and 31 July (T5 group) in 2022 and processed using natural drying and silage fermentation to evaluate fermentation quality, chemical composition, in vitro digestibility and vitamin content. Results: The fermentation quality of L. chinensis silage prepared at all five times of harvest was better. The silage fermentation group showed a significant increase (p<0.05) in crude protein (CP), thiamin, riboflavin, pyridoxine and α-tocopherol content, a significant decrease (p<0.05)in water -soluble carbohydrate (WSC) content, and small differences in neutral detergent fibre (NDF), acid detergent fibre (ADF), niacin and pantothenic acid content, when compared to the natural drying group. The content of thiamine, riboflavin, niacin, pantothenic acid and pyridoxine were higher in the pre-harvest period. In silage fermentation, the loss rate of thiamin, riboflavin and pyridoxine was positively correlated with pH and WSC, and the loss rate of thiamin and riboflavin was negatively correlated with lactic acid content. The loss rate of pantothenic acid was negatively correlated with pH and WSC, and positively correlated with lactic acid and ammonia nitrogen.The rate of α-tocopherol synthesis exceeded the rate of catabolism. Conclusions: The content of CP, thiamine, riboflavin, niacin, pantothenic acid and pyridoxine were higher during the early harvest period. Silage fermentation preserved the chemical composition and vitamin content of L. chinensis better than natural drying and had no effect on in vitro digestibility. During silage fermentation, the acidic environment promoted the preservation of thiamin, riboflavin and pyridoxine, but promoted the breakdown of pantothenic acid, α-tocopherol content increased through synthesis.